Corporate governance and corporate social responsibility of Spanish football clubs: current situation and options for the future - Arroyo Bravo, Francisco Javier; Fernández Fernández, José Luis; López Martínez, Raúl (Springer Nature Switzerland AG (Cham, Suiza), 2026)
El capítulo analiza la aplicación de la responsabilidad social corporativa y, de forma específica, del gobierno corporativo en el deporte profesional español, con especial atención a los clubes de fútbol. Desde una perspectiva institucional y jurídica, revisa los conceptos de responsabilidad social y buen gobierno, así como el marco normativo aplicable, incluida la legislación sobre transparencia y deporte. A partir de este contexto, el trabajo examina cómo las estructuras de gobierno, las presiones sociales y las expectativas de los grupos de interés influyen en la adopción de prácticas responsables por parte de las entidades deportivas. El capítulo combina reflexión teórica y orientación práctica para proponer medidas que favorezcan una gestión más transparente, sostenible y coherente con los valores sociales del deporte y con la sostenibilidad futura del fútbol como actividad económica e institución social.

This chapter examines the application of corporate social responsibility and, more specifically, corporate governance in Spanish professional sport, focusing on football clubs. From an institutional and legal perspective, it reviews the main concepts of CSR and good governance, together with the regulatory framework shaped by transparency and sports legislation. The chapter then applies these principles to the football sector, considering how governance structures, social pressure, and stakeholder expectations affect the adoption of responsible practices by clubs and sports entities. It combines theoretical discussion with practical implications and proposes measures aimed at improving transparency, accountability, and sustainable management. Overall, the chapter highlights the importance of good governance and CSR for building a sustainable business model around football, aligned with the social role that sport is expected to fulfil.
Capítulos en libros
Keywords: Cátedra Iberdrola de Ética Económica y Empresarial